Understanding flocculation properties of soil impurities present in the factory sugarcane supply. (November 2016) - Bakir, Hakan; Zhang, Zhanying; Zbik, Marek S.; Harrison, Mark D.; Doherty, William O.S.
Abstract: Soil impurities in sugarcane supplies affect clarification and filtration unit operations in the raw sugar manufacturing process. Juices expressed from the sugarcane plant grown in certain soils display poor clarification and dewatering behaviours. In this study, the salient features of these soils were determined in order to understand why they influence flocculation and settling of juice particles (flocs). The soils were characterized by X-ray powder diffraction, transmission-, transmission x-ray-, and scanning-electron microscopy, and their solution chemistries determined in electrolytes. In general, clay mineral composition, cation exchange capacity, and particle size contributed towards the poor settling characteristics of the soils. Fine particles ( i.e ., <200 nm) were found in difficult to clarify soil samples and were identified as nano-clays. The structure-building phenomenon of these clays if present in sugar juice are likely to impact on clarification, hindering the juice particles ability to settle despite changing environmental chemistry. Highlights: Structure building phenomenon may be responsible for poor juice clarification. Clay mineral composition impacted settling characteristics. Nano-clays were found in difficult to clarify soil samples.